2013
DOI: 10.1088/1748-9326/8/1/015004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling low-carbon US electricity futures to explore impacts on national and regional water use

Abstract: The US electricity sector is currently responsible for more than 40% of both energy-related carbon dioxide emissions and total freshwater withdrawals for power plant cooling (EIA 2012a Annual Energy Outlook 2012 (Washington, DC: US Department of Energy), Kenny et al 2009 Estimated Use of Water in the United States 2005 (US Geological Survey Circular vol 1344) (Reston, VA: US Geological Survey)). Changes in the future electricity generation mix in the United States will have important implications for water use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 16 publications
0
82
0
Order By: Relevance
“…Assuming comparable actions by other nations, the U.S. would have a carbon budget equivalent to emitting no more than~170-200 Gigatons of carbon dioxide between 2012 and 2050, a level consistent with the goal of reducing U. S. emissions by 83 % below 2005 levels by mid-century (NRC, 2010). A large proportion of these reductions will come from the power sector, and meeting this emissions goal will require extensive expansion of renewable energy (Fawcett et al 2009;Clemmer et al 2013). Staying within the U.S. carbon budget, for example, will require expansion of land-based wind energy from 60 GW in 2012 to 330-440 GW in 2050, and offshore wind expansion from zero currently to 25-100 GW; estimates for solar energy in 2050 range from 160-260 GW for photovoltaic and 20-80 GW for concentrated solar (Clemmer et al 2013).…”
Section: Need For Significant Renewable Energy Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming comparable actions by other nations, the U.S. would have a carbon budget equivalent to emitting no more than~170-200 Gigatons of carbon dioxide between 2012 and 2050, a level consistent with the goal of reducing U. S. emissions by 83 % below 2005 levels by mid-century (NRC, 2010). A large proportion of these reductions will come from the power sector, and meeting this emissions goal will require extensive expansion of renewable energy (Fawcett et al 2009;Clemmer et al 2013). Staying within the U.S. carbon budget, for example, will require expansion of land-based wind energy from 60 GW in 2012 to 330-440 GW in 2050, and offshore wind expansion from zero currently to 25-100 GW; estimates for solar energy in 2050 range from 160-260 GW for photovoltaic and 20-80 GW for concentrated solar (Clemmer et al 2013).…”
Section: Need For Significant Renewable Energy Expansionmentioning
confidence: 99%
“…Rapid, large-scale expansion of low-and zero-carbon renewable energy sources is essential for limiting the magnitude of global warming and its impacts on wildlife (Clemmer et al 2013). Expansion of renewable energy leads to concerns in the conservation community over harm to wildlife populations from injury and death of individual birds and bats or from fragmentation of species' habitat (e.g., Arnett & Baerwald 2013;Kiesecker et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This issue provides perhaps the most comprehensive and integrated effort to assess the water implications of electric power generation in the U.S., both at the national level and also with a high enough level of spatial resolution to assess watershed-level impacts. This issue includes the following sets of analyses: (a) a review of water factors from the primary literature [23 ] and comparison of reported and calculated water use [22]; (b) description of a linked energy and water modeling framework (ReEDS and WEAP) [44]; (c) modeling of low carbon electricity futures [37], with assessment of the water impacts of those scenarios at the national and regional level [34 ]; and (d) linking the results of the electricity scenarios with models of regional water systems for the southeastern U.S. [31,43] and southwestern U.S. [32,42].…”
Section: Long-term System-level Trends In Water For Energymentioning
confidence: 99%
“…Compared with natural gas which emits 0.6-2 lb of CO 2 Equivalent per kilowatt-hour (CO 2 E/kWh), and coal-1.4 to 3.6 lb of CO 2 E/kWh, solar energy emits only 0.07-0.2 lb of CO 2 E/kWh [1]. The use of renewable energy could replace the carbon intensive energy sources and helps in reducing the overall global warming.…”
Section: Introductionmentioning
confidence: 99%